Apuntes sobre la causal de anulación de laudos por materia no arbitrable, y su invocación de oficio - Arrarte Arisnabarreta, Ana María (2015)
This paper analyzes mainly the figure of the annulment of an arbitratien award for having ruled on a non-arbitrable matters and the power of judges to invoke this ground of trade. With that purpose , this paper also consider some important legal concepts as the nullity, the arbitrability and public order as well as the Peruvian Arbitration Act and the grounds for annulment of awards which is expected.